'Are you working or playing?' Investigating young children's perspectives of classroom activities. Issue 4 (2nd October 2017) - Breathnach, Helen; Danby, Susan; O'Gorman, Lyndal
ABSTRACT: Play is valued conceptually and pedagogically, although its place in early years settings is under increasing pressure. Framed by the sociology of childhood and understandings of children's agency, this article reports on an ethnographic study with children aged five years in the first year of primary school in Australia. The study investigated children's understandings of play in classroom activities involving different periods of teacher-framed and child-selected activities. Drawing on children's accounts and video-recorded observations, the study found that children's participation was influenced by teacher-framed agendas, and the agency afforded to them to engage in self-chosen activities and to design and negotiate their play spaces. For instance, children generally were unenthusiastic about writing activities and called these activities 'work' if they were directed by the teacher, and yet they consistently chose to engage in writing activities during periods of freely chosen activities. The findings raise questions about what counts as 'play' and 'work' for children, and the important function of play and free choice to mobilise participation in foundational academic activities such as writing. These understandings generate opportunities for educators to reflect upon ways to enhance children's participation in everyday play activities in the classroom as supporting foundational academic activities.